The 2018 Mw 6.8 Zakynthos (Ionian Sea, Greece) earthquake: seismic source and local tsunami characterization. Issue 2 (3rd February 2020) - Cirella, A; Romano, F; Avallone, A; Piatanesi, A; Briole, P; Ganas, A; Theodoulidis, N; Chousianitis, K; Volpe, M; Bozionellos, G; Selvaggi, G; Lorito, S
SUMMARY: We investigated the kinematic rupture model of the 2018 M w 6.8 Zakynthos, Ionian Sea (Greece), earthquake by using a non-linear joint inversion of strong motion data, high-rate GPS time-series and static coseismic GPS displacements. We also tested inversion results against tide-gauge recordings of the small tsunami generated in the Ionian Sea. In order to constrain the fault geometry, we performed several preliminary kinematic inversions by assuming the parameter values resulting from different published moment tensor solutions. The lowest cost function values were obtained by using the geometry derived from the United States Geological Survey (USGS) focal solution. Between the two conjugate USGS planes, the rupture model which better fits the data is the one with the N9°E-striking 39°ESE-dipping plane. The rupture history of this model is characterized by a bilateral propagation, featuring two asperities; a main slip patch extending between 14 and 28 km in depth, 9 km northeast from the nucleation and a slightly shallower small patch located 27 km southwest from the nucleation. The maximum energy release occurs between 8 and 12 s, when both patches are breaking simultaneously. The maximum slip is 1.8 m and the total seismic moment is 2.4 × 10 19 Nm, corresponding to a M w value of 6.8. The slip angle shows a dominant right-lateral strike-slip mechanism, with a minor reverse component that increases on the deeper region of the fault. This result, in addition to the observed possibility of similar mechanisms for previous earthquakes occurred in 1959 and 1997, suggests that the tectonic deformation between the Cephalonia Transform Fault Zone and the northern tip of the Hellenic Arc Subduction zone may be accommodated by prevailing right lateral low-dipping faults, occurring on re-activated structures previously experiencing (until Pliocene) compressional regime. Comparison of predicted and observed tsunami data suggests the need of a better characterization of local harbour response for this type of relatively short-wavelength events, which is important in the context of tsunami early warning. However, the suggested dominantly strike-slip character would in turn imply a reduced tsunami hazard as compared to a dominant thrust faulting regime from this source region.